2011
DOI: 10.4321/s0004-05922011000400035
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Carassius auratus with different food strategies in water recirculation system

Abstract: SUMMARYThe efficiency of a recirculation system for the cultivation of C. auratus, fed with natural and artificial diets was evaluated. The experiment consisted of four treatments with four replicates. The first two treatments used recirculation system and the last two static system. In the first and fourth treatment, animals were fed with brine shrimp biomass (50% CP), while in the second and third treatments a commercial flake ration (42% CP) was used. At the end of cultivation (60 days), water samples were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 31 publications
0
3
0
1
Order By: Relevance
“…Wallat et al (18) used six different commercial diets supplemented with different carotenoids and showed they have a variable effect on skin color and the growth of juveniles of Oranda of C. auratus. Moreira et al (19) reported that in feeding treatments with Artemia and comercial feed in flakes in a circulation system and another with a static system, they found significant differences in growth (weight and size) in animals fed with Artemia (at 60 days). Also, they mentioned that the animals that received Artemia had improved pigmentation, although they did not offer any data on this last point.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wallat et al (18) used six different commercial diets supplemented with different carotenoids and showed they have a variable effect on skin color and the growth of juveniles of Oranda of C. auratus. Moreira et al (19) reported that in feeding treatments with Artemia and comercial feed in flakes in a circulation system and another with a static system, they found significant differences in growth (weight and size) in animals fed with Artemia (at 60 days). Also, they mentioned that the animals that received Artemia had improved pigmentation, although they did not offer any data on this last point.…”
Section: Discussionmentioning
confidence: 99%
“…Wallat et al (18) utilizaron seis dietas comerciales diferentes suplementadas con diferentes carotenoides y demostraron que tienen un efecto muy variable en la coloración de la piel y el crecimiento de juveniles de la variedad de Oranda de C. auratus. Moreira et al (19) reportan que bajo tratamientos alimenticios con Artemia y alimento comercial en hojuelas y bajo un sistema de recirculación y otro estático, encontraron diferencias significativas en crecimiento (peso y talla) en los animales alimentados con Artemia (a los 60 días). También, mencionan que los organismos que recibieron Artemia incrementaron su pigmentación, aunque no ofrecen dato alguno sobre esto último.…”
Section: Discussionunclassified
“…In the excavated tanks, the combination of natural feeding with the fish-food provided better fish development, on average. Several authors have obtained better performance for post-larval fish through the combination of natural and artificial diets (Feiden, Hayashi, & Boscolo, 2006;Meurer, Boscolo, Hayashi, & Wolf, 2008;Moreira et al, 2011;Pedreira et al, 2015;Caldini, Cavalcante, Rocha Filho, & Carmo e Sá, 2015), and satisfactory results with the use of organic and/or inorganic fertilization to increase natural food in the tanks (Azim & Little, 2006;Sipaúba-Tavares & Braga, 2007). In both evaluated environments, the lowest means for the productive performance variables were obtained in the treatments with only fish-food, evidencing post-larvae's low capacity to assimilate the fish-food offered.…”
Section: Resultsmentioning
confidence: 99%
“…Goldfish originally from Asia is a resistant, omnivorous, and brightly colored species, frequently used as ornamental fish kept in domestic tanks [ 36 , 37 ]. This species can resist cold temperatures (close to 2 °C) and hypoxic conditions, also can tolerate brackish water [ 38 ].…”
Section: Methodsmentioning
confidence: 99%